Interest Rate Liberalization and Money Market Development - Mehran, Hassanali; Laurens, Bernard; Quintyn, Marc. (Washington, D.C. : International Monetary Fund, 1996)
This book by Hassanali Mehran, Bernard Laurens, and Marc Quintyn brings together the papers presented at a seminar held in Beijing, China, in August 1995 and sponsored jointly by the IMF's Monetary and Exchange Affairs Department and the Poeple's Bank of China. The papers were written by central bankers from China, Italy, Korea, Malaysia, Thailand, and Turkey. The Chinese authorities were specifically interested in learning more about the Italian and Turkish models of interbank markets and in the experiences of neighboring Asian countries with interest rate liberalization. The U.S. experience was also presented, and the introduction to the book draws policy lessons from the experiences presented at the seminar.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet